Analisis nilai tambah ciptaan nelayan pancing rawai dasar di Desa Bahari Kecamatan Sampolawa Kabupaten Buton Selatan - Fajrin; La Ola, La Onu; Kamri, Syamsul; Piliana, Wa Ode; Risfandi; Siang, Roslindah Daeng (Universitas Halu Oleo, 2023)
This study aims to determine the operating techniques of bottom longline fishing gear and determine the added value created by bottom longline fishing gear. This research was carried out in Bahari Village, Sampolawa District, South Buton Regency in July 2022. The method used in this study was the census method. Data collection was carried out through interviews, observation, documentation and literature studies. Data analysis uses the added value formula, namely NT=G+Pt+Pj+π. The results of the study concluded that the bottom longline fishing technique in Bahari Village was to go to the fishing location, place bait on each hook, release the bottom longline at a depth of 10-20 meters with fishing gear lengths varying from 900-1100 meters with a total of ±200 hooks for each fisherman and 3 units of buoys and left in the sea for 2-3 hours, as well as hauling (lifting fishing gear). This fishing gear is operated at low tide. The added value created by bottom longline fishing gear, the lowest value is Rp913.000,-/trip and the highest is Rp1.351.000,-/trip and the average is Rp1.179.850,-/trip, the added value obtained from the sum of Salaries, Depreciation, Taxes and Profits